Crispy Anchovy Processing in Amasing Village, South Halmahera Regency - Wulandari, Tri Laela; Darmawaty, Darmawaty; Rumaiga, Faizal; Abdulkadir, Irwan; Mutmainnah, Mutmainnah; Djamhur, Martini; Kaidati, Bahar; Azis, Muh. Aksa (Agrikan Jurnal Agribisnis Perikanan, 2023)
Amasing village, located in South Halmahera Regency, North Maluku Province, is predominantly inhabited by a fishing community. This village boasts abundant natural resources, particularly a bountiful population of anchovies in its surrounding waters. However, the residents of Desa Amasing face several challenges in harnessing these natural resources to improve their economy. Therefore, the objective of this community service initiative is to add value to the fishermen's catch, particularly anchovies, by processing them into high-value crispy anchovy products. This initiative also aims to develop Desa Amasing into a model village based on the creative economy, especially in anchovy processing. This approach has the potential to significantly increase the income of the local community. Furthermore, we are making efforts to promote and market these crispy anchovy products to the general public. The implementation method involves aligning the program team's perceptions with community needs, collaborating with housewives, providing training in crispy anchovy production and business management, and offering marketing support. As a result of these activities, the housewives in Desa Amasing have successfully processed anchovies and have also improved the packaging of crispy anchovy products, making them more appealing to potential consumers. This initiative represents a significant step in empowering the local community and enhancing their economic resilience.